Oxytocin Receptor Exon III Methylation in the Umbilical Cord Blood of Newborns With Prenatal Exposure to Crack Cocaine - Baptista, Talita; de Azeredo, Lucas Araújo; Zaparte, Aline; Viola, Thiago Wendt; Coral, Sayra Catalina; Nagai, Maria Aparecida; Mangone, Flávia Rotea; Pavanelli, Ana Carolina; Schuch, Jaqueline B.; Mardini, Victor; Szobot, Claudia M.; Grassi-Oliveira, Rodrigo (Frontiers in Cell and Developmental Biology, 2021)
Background Prenatal cocaine exposure (PCE) is associated with behavioral, cognitive, and social consequences in children that might persist into later development. However, there are still few data concerning epigenetic mechanisms associated with the effects of gestational cocaine exposure, particularly in human newborns. Aims We investigated the effects of PCE on DNA methylation patterns of the Oxytocin Receptor (OXTR) gene in the umbilical cord blood (UCB). The relationship between UCB DNA methylation levels and the severity of the mother’s cocaine use during pregnancy was also evaluated. Methods In this cross-sectional study, 28 UCB samples of newborns with a history of crack cocaine exposure in utero and 30 UCB samples of non-exposed newborns (NEC) were compared for DNA methylation levels at two genomic loci located in exon III of the OXTR gene (OXTR1 and OXTR2) through pyrosequencing. Maternal psychopathology was investigated using the Mini International Neuropsychiatric Interview, and substance use characteristics and addiction severity were assessed using the Smoking and Substance Involvement Screening Test (ASSIST). Results No differences between newborns with a history of PCE and NEC were observed in OXTR1 or OXTR2 DNA methylation levels. However, regression analyses showed that maternal addiction severity for crack cocaine use predicted OXTR1 DNA methylation in newborns. Conclusion These data suggest that OXTR methylation levels in the UCB of children are affected by the severity of maternal crack cocaine usage. Larger studies are likely to detect specific changes in DNA methylation relevant to the consequences of PCE.